Promosi Kesehatan Pencegahan Hipertensi Sejak Dini (ABDIMAS: Jurnal Pengabdian Masyarakat, 2018)
Hypertension is a condition which blood pressure is higher than 140/90 mmHg. Uncontrolled hypertension can cause a variety of diseases to the point of death. However, prevention of hypertension can be done early. Health Promotions aim to increase the knowledge of students in Ciamis District about prevention of hypertension. Health Promotion were carried out by explanation and discussion of 130 students in Ciamis District who were collected at WISMA GURU Ciamis on March 6, 2018. Before and after Health Promotion, participants were given a knowledge questionnaire and the results were processed using SPSS Version 16. Health Promotion instruments used flyers and power point presentation. Health Promotion of prevention of hypertension early has done successful and has a positive impact on increasing the knowledge of students and society.